Analysis of the Navy's Work Stress Factors in terms of Perception of the Physical Work Environment - Setyawan, Joko; Paryontri, Ramon Ananda (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
TNI members in this decade experienced an increase in stress. The stress experienced by Navy members is likely to be directly proportional to the conditions of their work environment which requires them to be firm, hard, and full of pressure that causes stress to Navy members which causes Navy members to be easily provoked by their emotions. This is due to the perception that Navy members are selected humans who can overcome any condition but in fact when faced with a poor physical environment, it will affect the performance of Navy members so that there is an expectation of individual survival of the work environment that is not directly proportional to the reality where Navy members are people who are easily exposed to stress if the physical work environment is negativeThe purpose of this study was to determine the relationship between the perception of the physical work environment and work stress in members of the Navy in the Juanda area, Surabaya. The study population was 60 people with purposive sampling techniques. The criteria used are members of the Navy who are married and work in the Surabaya area. The data collection method uses a scale of perception of the physical work environment and a scale of work stress. Data analysis using Pearson's Product Moment analysis technique. The results of data analysis on the sample subjects found that the correlation test of the variable perception of the physical work environment with work stress was =-0.569 where the results stated < 0.05 where the results stated < from 0.05 so that it shows that there is a negative correlation between the perception of the physical work environment and work stress in Navy members, so that the higher the perception of the work environment, the lower the work stress, also vice versa when Navy members have a low perception of the work environment, it will have an impact on high work stress.Anggota TNI dalam dekade ini mengalami peningkatan dalam stres. Stres yang dialami anggota TNI AL tersebut memiliki kemungkinan berbanding lurus dengan keadaan lingkungan kerja mereka yang mengharuskan untuk tegas, keras, dan penuh dengan tekanan sehingga menimbulkan stres pada anggota TNI AL yang menyebabkan anggota TNI AL tersebut mudah sekali untuk terpancing emosinya. Hal tersebut disebabkan oleh persepsi mengenai anggota TNI AL adalah manusia pilihan yang bisa mengatasi kondisi apapun tapi kenyataannya ketika dihadapkan dengan lingkungan fisik yang kurang baik, maka akan mempengaruhi kinerja anggota TNI AL sehingga terjadi harapan akan keberlangsungan hidup individu terhadap lingkungan kerja yang tidak berbanding lurus dengan realita dimana anggota TNI AL adalah orang yang mudah untuk terpapar stres jika lingkungan kerja fisiknya negatif. Populasi penelitian berjumlah 60 orang dengan teknik sampling purposive sampling. Kriteria yang digunakan adalah anggota TNI AL yang sudah menikah dan bekerja di wilayah Surabaya. Metode pengumpulan data menggunakan skala persepsi lingkungan kerja fisik dan skala stres kerja. Analisis data menggunakan teknik analisis Product Moment Pearson. Hasil analisis data pada subjek sampel diketahui bahwa uji korelasi variabel persepsi lingkungan kerja fisik dengan stres kerja sebesar =-0,569 dimana hasil yang dikemukakan < dari 0,05 sehingga hal itu menunjukkan bahwa adanya korelasi yang sifatnya negatif antara persepsi lingkungan kerja fisik dengan stres kerja pada anggota TNI AL, sehingga semakin tinggi persepsi lingkungan kerja maka semakin rendah stres kerja, juga sebaliknya ketika anggota TNI AL memiliki persepsi lingkungan kerja yang rendah maka akan berdampak pada stres kerja yang tinggi.